Timing earnings - Donghua Chen; Xiangqin Qi; Yongjian Shen; Huimiao Lin (China Journal of Accounting Research, 2011)
Since the opening of China’s securities market, there have been a number of bull and bear cycles. This paper discusses how executives use the market timing approach to manage earnings in different cycles to maximize firm value. We find that Chinese listed companies choose to release more earnings during bull markets and this phenomenon is more evident in companies that are more profitable and have higher valuations. We also find that executives who do not release more earnings during bull markets are more likely to be dismissed.